First-trimester choroid plexus-to-head ratio: a novel sonographic marker for the early detection of fetal central nervous system malformations - Xue, Xianghua; Tu, Peng; Zhang, Xiaohang; Ran, Suzhen; Zhang, Xuemei (Frontiers in Medicine, 2025)
BackgroundPrenatal diagnosis of nervous system malformations associated with the abnormal development of cerebrospinal fluid is most commonly made in the mid-trimester. During early gestation, the choroid plexus is the dominant structure occupying the lateral ventricles. Detection of abnormally positioned choroid plexuses within the fetal head may serve as a novel sonographic marker for the early identification of these malformations.MethodsThis was a retrospective study of singleton pregnancies with nervous system abnormalities. In the first trimester, the choroid plexus area (CPA), choroid plexus length (CPL), occipitofrontal diameter (OFD), head area (HA), head circumference (HC), abdominal circumference (AC), and the distance between the anterior margin of the choroid plexus (CP) and the medial side of the frontal bone (CFD) were measured in the transventricular axial plane. The ratios of CPA/HA, CPL/OFD, CFD/OFD, and HC/AC were also assessed.ResultsA total of 256 fetuses were included in the control group, and a reference range was established. In total, 52 cases with nervous system abnormalities associated with abnormal cerebrospinal fluid development were confirmed. In the control group, the ratios of CPA/HA and CPL/OFD decreased (r = −0.499, −0.216, respectively, both p < 0.001), while the CFD/OFD ratio increased (r = 0.445, p < 0.001). Compared with the control group, scatter diagrams and box-and-whiskers plots showed ventriculomegaly (VM) fetuses had significantly decreased CPA/HA and CPL/OFD ratios (p < 0.001), but increased CFD/OFD and HC/AC ratios (p < 0.001). The CPA/HA, CPL/OFD, and CFD/OFD ratios were all significantly higher in fetuses with open spina bifida (OSB) (p < 0.05). Fetuses with microcephaly showed a significantly higher CPA/HA ratio (p < 0.001), higher CPL/OFD ratio (p < 0.001), and lower HC/AC ratio (p < 0.05).ConclusionChoroid-plexus-to-head ratios offer an objective means of assessing nervous system malformations associated with abnormal cerebrospinal fluid development during the first trimester.